Integrasi BIM 5D pada Perencanaan Ulang Struktur Bangunan Gedung Parkir Dinas Teknis Jatibaru - Nur Hafshah; Naura Rahma Pramudhita; Bambang Setiabudi; Anita Lestari Condro Winarsih (Universitas Diponegoro, 2025)
Building Information Modeling (BIM) is an integrated digital method that enhances efficiency in construction project management by combining planning, execution, and control elements. This study utilizes the BIM 5D approach, which integrates 3D modeling, scheduling, and cost estimation, to redesign the structural system of a multi-story parking building using a Moment Resisting Frame (SRPM) as an earthquake-resistant structural system. The main focus of this research is to produce a more accurate and efficient Bill of Quantities (BoQ) and cost estimation through data integration from Revit, Microsoft Project, and Navisworks. The structural model is developed in Revit to generate a detailed three-dimensional representation, followed by scheduling in Microsoft Project. Subsequently, all cost-related data is imported into Navisworks for quantity takeoff and automated cost analysis. The results indicate that the application of BIM 5D significantly improves the accuracy of BoQ preparation and supports more effective decision-making in project planning. These findings can serve as a reference for optimizing cost planning processes in high-rise construction projects, particularly those designed for seismic resilience in Indonesia.